Prediction of esophageal varices and risk of bleeding in liver cirrhosis by aspartate aminotransferase to-platelet ratio index and fibrosis-4 index - Kumar, Shailesh; Kumar, Vinay; Giri, Richa; Agarwal, Saurabh; Gautam , S. K. (International Journal of Advances in Medicine, 2023)
Background: Liver cirrhosis is the end-stage for chronic liver disease. During the course of cirrhosis repeated endoscopy is recommended. As this intervention is expensive and often poorly accepted by patients who may refuse further follow up, there is a need for non-invasive methods to predicts the progression of portal hypertension as well as the presence and size of esophageal varices. This study was aimed to assess the value of aspartate aminotransferase (AST)-to-platelet ratio index (APRI) and fibrosis-4 index (FIB-4) for predicting esophageal varices in cirrhotic patients. Objectives of the study were: prediction of esophageal varices and risk of bleeding in liver cirrhosis by APRI, and prediction of esophageal varices and risk of bleeding in liver cirrhosis by FIB-4. Methods: It was a single centre, observational study in 100 patients of chronic liver disease. Patients were included in the study after applying inclusion and exclusion criteria. Complete blood count (CBC), liver function test (LFT), kidney function test (KFT), SE, viral marker, ultrasonography (USG) whole abdomen, and upper gastrointestinal endoscopy (UGIE) was done for all patients. Child-Pugh-Turcotte (CTP) score was calculated for every patient. Results: The APRI and FIB-4 shows moderate diagnostic accuracy in predicting the presence of esophageal varices and variceal bleed. Conclusions: In conclusion, the APRI and FIB-4 shows moderate diagnostic accuracy in predicting the presence of esophageal varices and variceal bleed. They help in starting prophylactic therapy earlier to prevent the bleeding and other complications of varices. Although endoscopy remains the primary modality for diagnosis of esophageal varices but these non-invasive parameters can also play an effective role in conjunction with endoscopy in predicting the presence of esophageal varices.